Ù¾ÚÙÙØ´Û ÙÙÙÛ Ø¯Ø± ÙØ³Ø¦ÙÛ ÙØµØ§Øµ ÙØ§Ø¯Ø± Ø¯Ø± ÙØªÙ ÙØ±Ø²ÙØ¯ - Ã˜ÂÃ˜Â§Ã˜Â¦Ã˜Â±Ã›ÂŒ, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯Ã˜ÂÃ˜Â³Ã™Â†; Ã™Â…Ã˜Â±Ã˜Â§Ã˜Â¯Ã›ÂŒ ÃšÂ¯Ã™Â„Ã˜Â³Ã˜ÂªÃ˜Â§Ã™Â†Ã›ÂŒ, Ã™Â…Ã˜Â±Ã˜ÂªÃ˜Â¶Ã›ÂŒ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
According to the viewpoints of the two major sects (ShÄ«âa and SunnÄ«) and the article 221 of the Islamic penal law, the verdict of retaliation (qiá¹£Äá¹£) in deliberate murder does not apply to a father who has murdered his child; however, according to the generally accepted view of the ImÄmiyya, the mother is not excluded from this verdict and is retaliated in qiá¹£Äá¹£ for murdering her child. Setting forth and examining the legal evidences of both viewpoints, the writers of this article have to a great extent regarded the exclusion of the mother from this verdict as justified and defendable with respect to the evidences.